Exploratory Study of a CT Radiomics Model for the Classification of Small Cell Lung Cancer and Non-small-Cell Lung Cancer - Liu, Shihe; Liu, Shunli; Zhang, Chuanyu; Yu, Hualong; Liu, Xuejun; Hu, Yabin; Xu, Wenjian; Tang, Xiaoyan; Fu, Qing (Frontiers in Oncology, 2020)
Background: Radiomics can quantify tumor phenotypic characteristics non-invasively by applying feature algorithms to medical imaging data. In this study,we investigated the association between radiomics features and the tumor histological subtypes,and we aimed to establish a nomogram for the classification of small cell lung cancer (SCLC) and non-small-cell lung cancer (NSCLC). Methods: This was a retrospective single center study.In total, 468 cases including 202 patients with SCLC and 266 patients with NSCLC were enrolled in our study, and were randomly divided into a training set (n=327) and a validation set (n=141) in a 7:3 ratio. The clinical data of the patients, including age, sex, smoking history, tumor maximum diameter, clinical stage and serum tumor markers, were collected. All patients underwent enhanced computed tomography (CT) scans, and all lesions were pathologically confirmed. A radiomics signature was generated from the training set using the least absolute shrinkage and selection operator algorithm. Independent risk factors were identiﬁed by multivariate logistic regression analysis, and a radiomics nomogram based on the radiomics signature and clinical features was constructed. The capability of the nomogram was evaluated in the training set and validated in the validation set. Results: Fourteen of 396 radiomics parameters were screened as important factors for establishing the radiomics model. The radiomics signature performed well in differentiating SCLC and NSCLC, with an area under the curve (AUC) of 0.86 (95% CI: 0.82-0.90) in the training set and 0.82 (95%CI: 0.75-0.89) in the validation set. The radiomics nomogram had better predictive performance (AUC=0.94 (95%CI: 0.90-0.98) in the validation set) than the clinical model (AUC= 0.86 (95%CI: 0.80-0.93)) and the radiomics signature (AUC=0.82 (95%CI: 0.75-0.89)), and the accuracy was 86.2% (95%CI: 0.79-0.92) in the validation set. Conclusion: The enhanced CT radiomics signature performed well in the classification of SCLC and NSCLC. The nomogram based on the radiomics signature and clinical factors has better diagnostic performance for the classification of SCLC and NSCLC than the simple application of the radiomics signature.